Hepatic Steatosis, Rather Than Underlying Obesity, Increases the Risk of Infection and Hospitalization for COVID-19 - Roca-Fernández, Adriana; Dennis, Andrea; Nicholls, Rowan; McGonigle, John; Kelly, Matthew; Banerjee, Rajarshi; Banerjee, Amitava; Sanyal, Arun J. (Frontiers in Medicine, 2021)
Objective Obesity is a risk factor for SARS-COV2 infection and is often associated with hepatic steatosis. The aim of this study was to determine if pre-existing hepatic steatosis affects the risk of infection and severity for COVID-19. Design Prospective cohort study (UK Biobank). Univariate and stepwise multivariate logistic regression analyses were performed on liver phenotypic biomarkers to determine if these variables increased risk of testing positive and being hospitalized for COVID-19; then compared to previously described risk factors associated with COVID-19, including age, ethnicity, gender, obesity, socio-economic status. Setting UK biobank study Participants 502,506 participants (healthy at baseline) in the UK Biobank, of whom 41,791 underwent MRI (aged 50-83) for assessment of liver fat, liver fibro-inflammatory disease and liver iron. Positive COVID-19 test was determined from UK testing data, starting in March 2020 and censored in January 2021. Primary and secondary outcome measures Liver fat measured as proton density fat fraction (PDFF %) MRI and body mass index (BMI, Kg/m2) to assess prior to February 2020 using MRI of the liver to assess hepatic steatosis. Results Within the imaged cohort (n=41, 791), 4458 had been tested and 1043 (2.49% of the imaged population) tested positive for COVID-19. Individuals with fatty liver (≥10%) were at increased risk of testing positive (OR:1.35, p=0.007) and those participants with obesity and fatty liver, were at increased risk of hospitalization with a positive test result by 5.14 times (p=0.0006). Conclusions UK Biobank data revealed obese individuals with fatty liver disease were at increased risk of infection and hospitalization for COVID-19. Public policy measures and personalized medicine should be considered in order to protect these high-risk individuals.